"Born Under My Heart": Adoptive Parents' Use of Metaphors to Make Sense of Their Past, Present, and Future. (January 2022) - Hackenburg, Lucas; Morgan, Toni; Brank, Eve
Metaphors provide the opportunity to make sense of our experiences and share them with others. The current research qualitatively examined interviews with adoptive parents who had adopted through intercountry or private adoptions. Throughout their interviews, each participant used at least one metaphor in describing their experiences of adopting and raising their child. Overarchingly, the metaphor of "Adoption is a journey" encapsulated parents' experiences. To demonstrate the journey, parents used metaphors to describe the past, present, and future. Metaphors of the past focused on their child's trauma and the origin of how the child came to join their family. Metaphors used to describe the present were challenge metaphors, including child's behaviors and finding support, coping metaphors, and balance metaphors. Lastly, metaphors of the future included guiding and commitment metaphors. In addition to metaphors, parents used symbolic rituals to connect their children with their past and current family. From metaphors, we offer several practical implications for postadoption intervention. First, interventions should be developed to meet participants where they are. Second, interventions should focus on the overall picture of adoption, as parents make sense of their past experiences and their ideals about the future. Lastly, services should focus on tools, not fixes.